Are the associative schemes possible in the country in particular rap? (2017)
The planning process has taken on a great importance in the new public administration, due mainly to the fact that this new administration is aimed at results and planning as the ultimate goal of evaluating and measuring the effects and results of public policies plied by governments. In Colombia, attempts have been made to improve this planning process in state entities. In addition, strategies have been developed to carry out inter-territorial planning such as associative schemes, schemes, characteristics, advantages and, in particular, the possibility of achieving special regions of Planning is the central theme of this essay.